2008
DOI: 10.2146/ajhp070391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacists on medication errors in an emergency department

Abstract: The rate of medication errors in the ED decreased significantly when pharmacists prospectively reviewed ED medication orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 13 publications
2
75
0
1
Order By: Relevance
“…In that study, a retrospective comparison of medical records for a control group (no pharmacist present in the emergency department) and an intervention group (pharmacist present in the emergency department to review orders) showed a 66% reduction in medication errors when the pharmacist was present. 19 In the current study, the main purpose of having the pharmacist in the Emergency Department was to complete medication histories and perform reconciliation; however, the pharmacist was also able to answer drug information questions, clarify poorly written orders, suggest alternatives to nonformulary medications, and identify unknown medications brought in by patients. As a result of this pilot project, a permanent pharmacist position has been created for the Emergency Department.…”
Section: Discussionmentioning
confidence: 96%
“…In that study, a retrospective comparison of medical records for a control group (no pharmacist present in the emergency department) and an intervention group (pharmacist present in the emergency department to review orders) showed a 66% reduction in medication errors when the pharmacist was present. 19 In the current study, the main purpose of having the pharmacist in the Emergency Department was to complete medication histories and perform reconciliation; however, the pharmacist was also able to answer drug information questions, clarify poorly written orders, suggest alternatives to nonformulary medications, and identify unknown medications brought in by patients. As a result of this pilot project, a permanent pharmacist position has been created for the Emergency Department.…”
Section: Discussionmentioning
confidence: 96%
“…30,31 This drive to perfection in job performance may also be intuited from the proliferation of pharmacy research papers examining numbers of medication errors in various settings, so that they can be minimized. [32][33][34] Openness, the third trait with a relatively strong difference in response frequencies, is characterized by originality, ingenuity, curiosity, and an artistic orientation. 13 Within work settings, people who exhibit this trait also tend to be drawn to artistic or investigative types of work.…”
Section: Discussionmentioning
confidence: 99%
“…One way to achieve true change and overcome the barriers would be to perform studies that can demonstrate how a pharmacist could produce better clinical and economic outcomes to patient care. Numerous studies have found that pharmacists can improve patient safety and outcomes [14][15][16][17][18][19][20][21][22][23]. However, no study has been performed in Iran, because clinical pharmacy is a new profession and at the moment, only a few clinical pharmacists are practicing in this country.…”
Section: Discussionmentioning
confidence: 99%